(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Leadership is the process of influencing the behavior of others regarding the accomplishment of goals in a given situation. It also refers to lifting a person’s performance to a higher standard, which builds a personality beyond his/her normal limitation. Leadership is the action of leading a group of people or an organization. Leaders help themselves and others to do the right things. They set direction, build an inspiring vision, and create something new. Leadership is about planning where you need to go to “win” as a team or an organization and to make the process dynamic, exciting, and inspiring. Leadership is an important function of management, which helps to maximize efficiency and achieve organizational goals. A leader is a person who starts the workby communicating the plans and the members from where the work starts. The researchers used a questionnaire to gather information about the effects of leadership skills and academic performances of selected officials in Grade 11 Humanities and Social Sciences Strand students, which were selected through purposive sampling. Results showed that written communication affected the composite averages for variable written works, with an average of 4.41. Verbal interpretation agreed with the positive effect of leadership skills in academic performances. The composite average for variable written works was 1.57, with verbal interpretation disagreeing with the negative effect of recitation in leadership skills. The researchers found out that the leadership skills had an impact on the academic performance of the elected officials. The leader should face the challenges and answer the consequences of the discussions. Then, you should be a good listener and observer to your coworkers. A leader should also trust her or his coworker or groupmate to finish the task that he or she gave.